Ciprofloxacin-imprinted polymeric receptors as ionophores for potentiometric transduction - Oliveira, Helena M.V. (2011)
A 3D-mirror synthetic receptor for ciprofloxacin host–guest interactions and potentiometric transduction is presented. The host cavity was shaped on a polymeric surface assembled with methacrylic acid or 2-vinyl pyridine monomers by radical polymerization. Molecularly imprinted particles were dispersed in 2-nitrophenyl octyl ether and entrapped in a poly(vinyl chloride) matrix. The sensors exhibited a near-Nernstian response in steady state evaluations. Slopes and detection limits ranged from 26.8 to 50.0 mV decade−1 and 1.0 × 10−5 to 2.7 × 10−5 mol L−1, respectively. Good selectivity was observed for trimethoprim, enrofloxacin, tetracycline, cysteine, galactose, hydroxylamine, creatinine, ammonium chloride, sucrose, glucose, sulphamerazine and sulfadiazine. The sensors were successfully applied to the determination of ciprofloxacin concentrations in fish and in pharmaceuticals. The method presented offered the advantages of simplicity, accuracy, applicability to colored and turbid samples and automation feasibility, as well as confirming the use of molecularly imprinted polymers as ionophores for organic ion recognition in potentiometric transduction.